Brokering web services...the next big thing? write a service and get rich. - Linthicum, David (SOA webservices journal.)
Web services were created around the notion that it's easier to discover and leverage somebody else's service rather than write your own from scratch. Also, it is much easier to create applications made up of many services, thereby allowing change to occur at a pace faster than anything we've seen in the industry thus far.